THE APPLICATION OF DISCOURSE-DISCUSSION METHOD AND STUDENT’S RESPONSE DURING THE NEW NORMAL ERA ON TEACHING SPEAKING - Putri, Trikaloka Handayani; Fauziyah, Nailul; Tiawati, Susi Nur (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2022)
New normal is a change in behavior or habits to maintain normal activities by always applying health protocols in the middle of the covid-19 pandemic. The covid-19 pandemic has an impact on the teaching and learning process, especially on the teacher teaching speaking method. The purpose of this study is to (1)describe how the teacher applies the learning method in teaching speaking during offline learning new normal era and (2)describe students respond to the teaching speaking method during offline learning new normal era. This research has expounded to explore the teacher’s methods used during the new normal era. This current study applied descriptive qualitative with teacher teaching speaking method during the new normal era. The data were collected by interview, observation checklist, and questionnaire. The Interview was done to the English teacher as the participant of this study, to get information about the differences in the learning activity during the covid-19 pandemic. The interview and observation checklist was done to get the teacher's teaching method during the new normal era. And the questionnaire was done to get the students' respond with the teacher teaching speaking method during the new normal era. The subject of this research were students and the English teacher of SMK Telkom Darul Ulum Jombang. And, the result of this study showed that in applying discourse-discussion method the teacher conducted the following steps, introduction and review, Information presentation, Monitor understanding, and Alignment. Then, there were 3 types of responses found, cognitive response, affective response, and conative response.